2018
DOI: 10.2147/cia.s182318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of functional dependence in Chinese centenarians and its relationship with serum vitamin D status

Abstract: BackgroundFunctional dependence (FD) and vitamin D deficiency are common conditions in older adults. However, little is known about the relationship between FD and serum vitamin D status in centenarians. The current study was designed to evaluate the prevalence of FD and examine its relationship with serum vitamin D status among centenarians in China.Subjects and methodsA cross-sectional study of a large sample of Chinese centenarians including 180 men and 822 women was conducted from June 2014 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Items of the Barthel index are regarded as dependent if they are performed with any help from other people. In our previous study, the functional dependence of ADL of centenarians was 71.2% (46).…”
Section: The Barthel Index For Activities Of Daily Livingmentioning
confidence: 79%
“…Items of the Barthel index are regarded as dependent if they are performed with any help from other people. In our previous study, the functional dependence of ADL of centenarians was 71.2% (46).…”
Section: The Barthel Index For Activities Of Daily Livingmentioning
confidence: 79%
“…Therefore, the CHCCS provides a good model for investigating aging and longevity in community-dwelling centenarians. Our previous work suggested that the serum 25(OH)D level might be associated with activities of daily living, functional dependence, and symptoms of depression at baseline in participants in the CHCCS [ 27 , 28 , 29 ]. In the present study, we further demonstrated that not only the 25(OH)D level but also the PTH and β-CTX levels were associated with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The Barthel Index of activities of daily living has been widely used to evaluate the physical function of centenarians (21,38); the validity and reliability of this tool for use in the Chinese population of older people have been well-established (39). The Barthel Index consists of 10 items measuring a person's PADLs, such as grooming, feeding, dressing, bathing, toilet use, transferring from bed to chair, walking, stair climbing, bowel continence, and urinary continence.…”
Section: Physical Activities Of Daily Living (Padls)mentioning
confidence: 99%
“…Previous studies suggested that circulating 25-hydroxyvitamin D [25(OH)D], a major circulatory form of vitamin D (15), as an independent determinant for physical dependence (PD) (16)(17)(18)(19)(20) in older people, including centenarians (21). Pathophysiological mechanisms include its beneficial roles in skeletal muscle regeneration (22), arterial stiffness and endothelial function (23,24), and immune regulation (25) etc.…”
Section: Introductionmentioning
confidence: 99%